Acoustic justice listening, performativity, and the work of reorientation - LaBelle, Brandon 1969- (Bloomsbury Academic, 2021)
Acoustic Performativity : Practices of Composition -- Poetic Ecologies : Resonance, Imagination, Repair -- Skin-Work : Queer Acoustics, Borderspaces, Economies of Desire -- Deaf Attention : Peripheral Visions, Spatial Meanings, Sensory Politics
Includes bibliographical references and index
Keywords: Musikhören; Musiksoziologie; Sound Studies; Gerechtigkeit; Music / Social aspects; Sound / Social aspects; Sound art / History and criticism; Justice (Philosophy); Listening (Philosophy)